A case series of adult intussusception diagnosed by ultrasound in South India: an uncommon notion - Vinoth, D.; Rajeshkumar, S.; Abu Sali, Sheik Asik (International Surgery Journal, 2020)
Intussusception is the telescoping of one segment of the gastrointestinal tract into an adjacent one. Adult intussusception is less than 0.1% of all hospital admissions. Non-specific symptoms often delay the diagnosis with most cases diagnosed only after emergency laparotomy, hence the need for imaging as a screening investigation. The gold standard is computed tomography with the limitations of cost, radiation and contrast hazards. Our suggested initial screening tool is ultrasound. the aim of this study was to evaluate the sensitivity of ultrasound in diagnosing this rare entity. Thirteen patients (2013 to 2019) in a single tertiary care hospital diagnosed as “intussusception” were analysed. They were initially diagnosed by ultrasound and confirmed by CT or intra-op as needed. There were no exclusion criteria. The mean age was 50. There were 6 males and 7 females. Ultrasound sensitivity was 72%. Symptoms were variable. 100% had abdominal pain (1 day to 2 years duration). 69% had Intestinal obstruction. The most common type of adult intussusception observed was ileo-ileal (39%). The least common noted was gastro-jejunal (8%). The most common treatment was resection and anastomosis (77%). 3 cases were managed conservatively successfully. The biopsy was mostly benign (54%), 3 were malignant (23%) and 3 were unknown as they were not operated (23%). Our suggested initial screening is ultrasound with a fairly good sensitivity (72%). The upcoming improvement in technology can raise this sensitivity even further. The management protocols, biopsy findings, and clinical findings are however subjected to discretion.